Urban gardening and its associations with diet and health in Palau facing an obesity crisis - Akiko Iida; Chihiro Tsuchiya-Theorin; Yin Yin Nwe; Takahiro Yamazaki; Ngirbechat Arsenio; Christopher Kitalong; Makoto Yokohari; Takuro Furusawa (npj Urban Sustainability, 2026)
Abstract Despite growing evidence of urban gardening’s health benefits, studies in the Pacific Islands facing an obesity crisis remain extremely limited. In Palau, compared with non-gardeners, urban gardeners had a 0.86-point higher dietary diversity score ( p < 0.001 ), 2.92 kg/m 2 lower BMI ( p = 0.011 ), and 3.49-fold higher odds of reporting good health ( p < 0.001 ). These findings suggest the importance of integrating urban gardening into public health and spatial strategies.